2016
DOI: 10.1021/acsami.6b00657
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Covalent Triazine Framework Membrane for Helium Separation and Hydrogen Purification

Abstract: Ultrathin membranes with intrinsic pores are highly desirable for gas separation applications, because of their controllable pore sizes and homogeneous pore distribution and their intrinsic capacity for high flux. Two-dimensional (2D) covalent organic frameworks (COFs) with layered structures have periodically distributed uniform pores and can be exfoliated into ultrathin nanosheets. As a representative of 2D COFs, a monolayer triazine-based CTF-0 membrane is proposed in this work for effective separation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 67 publications
2
67
0
1
Order By: Relevance
“…[24] CTFs have found various applicationss uch as catalysts for the electrochemical oxygen reduction reaction, [25] catalyst carriers, [26] gas separation and purification, [27] and others, [28][29][30] however,t oo ur knowledge,t hey have not been effectively ex-plored as enzyme mimics so far.Incomparison with the reported nanomaterial, CTFs may be as uperior material for the construction of peroxidase mimics. [24] CTFs have found various applicationss uch as catalysts for the electrochemical oxygen reduction reaction, [25] catalyst carriers, [26] gas separation and purification, [27] and others, [28][29][30] however,t oo ur knowledge,t hey have not been effectively ex-plored as enzyme mimics so far.Incomparison with the reported nanomaterial, CTFs may be as uperior material for the construction of peroxidase mimics.…”
Section: Introductionmentioning
confidence: 99%
“…[24] CTFs have found various applicationss uch as catalysts for the electrochemical oxygen reduction reaction, [25] catalyst carriers, [26] gas separation and purification, [27] and others, [28][29][30] however,t oo ur knowledge,t hey have not been effectively ex-plored as enzyme mimics so far.Incomparison with the reported nanomaterial, CTFs may be as uperior material for the construction of peroxidase mimics. [24] CTFs have found various applicationss uch as catalysts for the electrochemical oxygen reduction reaction, [25] catalyst carriers, [26] gas separation and purification, [27] and others, [28][29][30] however,t oo ur knowledge,t hey have not been effectively ex-plored as enzyme mimics so far.Incomparison with the reported nanomaterial, CTFs may be as uperior material for the construction of peroxidase mimics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, f tunn (T ) is a correction for tunneling effects along the reaction path. 22,42,43 Finally, γ is a correction factor (not considered previously) related to the fact that only a fraction of the membrane is effective for permeation 44 and is defined as…”
mentioning
confidence: 99%
“…Li and co‐workers predicted that 2D covalent‐triazine‐framework membranes (CTF‐0) with uniform and ultrasmall pores could work effectively for helium separation. From first‐principles calculations, it was found that a monolayer CTF‐0 membrane could exhibit unprecedentedly high helium selectivity over other permanent gases …”
Section: Gas Separation With Microporous Organic Membranesmentioning
confidence: 99%